2003
DOI: 10.1016/s0378-1097(02)01116-3
|View full text |Cite
|
Sign up to set email alerts
|

Different cellular fatty acid pattern behaviours of two strains of Listeria monocytogenes Scott A and CNL 895807 under different temperature and salinity conditions

Abstract: Cells of two strains of Listeria monocytogenes CNL 895807 and Scott A were grown to late exponential phase at different growth temperatures (37, 20 and 4 ‡C) with or without NaCl (7%), and their fatty acid compositions were analysed. The results showed that low thermal adaptation response of L. monocytogenes CNL was different than that of the Scott A strain, and it was based on both an increase of anteiso-branched-chain fatty acids and a significant decrease of straight-chain fatty acids. However, the main mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 15 publications
5
25
0
1
Order By: Relevance
“…2, bottom left panel). A similar shift towards production of anteiso fatty acids has been observed in response to salt stress with Listeria monocygotenes and several halotolerant bacteria (reference 10 and references therein); the resulting increase in membrane permeability was explained as a mechanism to facilitate adaptation to hyperosmotic conditions (10). Reinspection of PLFA results from the laboratory study re- (38) showed a consistent reduction of i15:0/ a15:0 ratios after urea amendment corresponding to the HU treatment but not after urea amendment corresponding to the LU treatment (data available upon request).…”
Section: Discussionsupporting
confidence: 62%
“…2, bottom left panel). A similar shift towards production of anteiso fatty acids has been observed in response to salt stress with Listeria monocygotenes and several halotolerant bacteria (reference 10 and references therein); the resulting increase in membrane permeability was explained as a mechanism to facilitate adaptation to hyperosmotic conditions (10). Reinspection of PLFA results from the laboratory study re- (38) showed a consistent reduction of i15:0/ a15:0 ratios after urea amendment corresponding to the HU treatment but not after urea amendment corresponding to the LU treatment (data available upon request).…”
Section: Discussionsupporting
confidence: 62%
“…Analysis of fatty acid methyl esters was performed using a Shimadzu GC14A gas chromatograph (Courtaboeuf, France) as previously described (Chihib et al 2003). At least two samples were withdrawn for each challenge condition and each experiment was done in triplicate.…”
Section: Fatty Acid Analysismentioning
confidence: 99%
“…Indeed, bacterial membranes must present a particular state of fluidity and integrity in order to ensure vital functions such as the maintenance of a proton-motive force or the active transport of metabolites (Russell 2002). The membrane lipid fatty acids of L. monocytogenes are characterised by a high proportion of iso and anteiso branched fatty acids (Raines et al 1968;Jula´k et al 1989), and it is established that the ai15:0 fatty acid plays a critical role in the growth at low temperature (Annous et al 1997;Chihib et al 2003). However, we demonstrated in our previous work that two reference strains of L. monocytogenes (Scott A and CNL 895807) presented different cellular lipid fatty acid patterns at low temperatures (Chihib et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Listeria is characterized by Ͼ85% branched-chain fatty acids (FA), anteiso-15:0 (a-15:0) and anteiso-17:0 (a-17:0). Cells grown in the cold (5°C) contain significantly less a-17:0 than those grown at higher temperatures (4,8,37,43,44,57). A cryotolerance element of Listeria is also its ability to use cryoprotectant osmolytes (31), a property shared by other organisms (2,3,12,21,23).…”
mentioning
confidence: 99%